The Effectiveness of STEM-Integrated Blended Learning on Indonesia Student Scientific Literacy: A Meta-analysis (International Journal of Education and Literature, 2023)
This study aims to determine the effectiveness of STEM-integrated blended learning on Indonesian students' science literacy. This research is a type of meta-analysis research. The data sources in the study came from the analysis of 10 national and international journals published from 2017-2023. The data search process through searching on Google Scholar, Scopus, Wiley, Eric and Hindawi Journal. Data collection techniques in research through direct observation by tracing studies related to research variables. The keywords in this article search are blended learning, STEM and science literacy. Data analysis technique is descriptive quantitative analysis technique with JSAP application. The results concluded that STEM-integrated blended learning is effective in encouraging the level of science literacy of students in Indonesia with an effect size value of 0.71 and N-gain of 0.82. Blended learning greatly supports the learning process in Indonesia in improving students' literacy in learning.